CONSUMER AWARENESS TOWARDS GST IN URBAN AND RURAL AREAS IN KANYAKUMARI DISTRICT - S.Santhiya Savithri; R. Samundeswari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The implementation of the Goods and Services Tax (GST) in India represents a landmark reform aimed at unifying the nation’s indirect tax structure. This study seeks to examine the level of consumer awareness towards GST in both urban and rural areas of Kanyakumari District, Tamil Nadu. Despite several years since its rollout, discrepancies in awareness and understanding of GST still persist, particularly between urban and rural populations. The objective of this research is to evaluate consumers’ knowledge of GST rates, its application on goods and services, and their perceptions of its impact on day-to-day expenses.A primary survey was conducted with a sample size of 110 respondents, comprising both urban and rural residents of Kanyakumari District. The study revealed that urban consumers possess a higher level of awareness and better access to information regarding GST, largely due to greater exposure to media and digital platforms. Conversely, rural consumers displayed limited awareness, with many relying on informal sources or facing challenges in understanding the technical aspects of the tax.The findings highlight the need for targeted awareness programs to bridge the knowledge gap and promote GST literacy in rural areas. The study recommends the use of regional language materials, community-level campaigns, and collaboration with local bodies to improve understanding and acceptance of GST among rural consumers. This research offers valuable insights into the effectiveness of GST outreach in a diverse district like Kanyakumari and underlines the importance of inclusive tax education for policy success